2006
DOI: 10.1161/circulationaha.105.581884
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Defibrillator Therapy or Amiodarone in Chronic Stable Heart Failure

Abstract: cardioverter-defibrillator (ICD) therapy significantly reduced all-cause mortality rates compared with medical therapy alone in patients with stable, moderately symptomatic heart failure, whereas amiodarone had no benefit on mortality rates. We examined long-term economic implications of these results. Methods and Results-Medical costs were estimated by using hospital billing data and the Medicare Fee Schedule. Our base case cost-effectiveness analysis used empirical clinical and cost data to estimate the life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(147 citation statements)
references
References 16 publications
(20 reference statements)
4
140
1
2
Order By: Relevance
“…1,2 Analysis of SCDHeFT demonstrated an incremental cost-effectiveness ratio Ͻ$100 000 only by extrapolating 3 years beyond the end of trial follow-up ($127 503 per life-year saved at 5 years and $88 657 at 8 years). 6 Analysis of MADIT II estimated a less favorable incremental cost-effectiveness ratio of $235 000 per life-year saved at 3.5 years. 7 These cost-effectiveness figures are particularly concerning for a therapy that has significant morbidity both at implantation and during longterm follow-up.…”
Section: Article See P 835mentioning
confidence: 99%
“…1,2 Analysis of SCDHeFT demonstrated an incremental cost-effectiveness ratio Ͻ$100 000 only by extrapolating 3 years beyond the end of trial follow-up ($127 503 per life-year saved at 5 years and $88 657 at 8 years). 6 Analysis of MADIT II estimated a less favorable incremental cost-effectiveness ratio of $235 000 per life-year saved at 3.5 years. 7 These cost-effectiveness figures are particularly concerning for a therapy that has significant morbidity both at implantation and during longterm follow-up.…”
Section: Article See P 835mentioning
confidence: 99%
“…The use of devices-biventricular pacemakers and ICDs with biventricular pacing capabilities-in addition to aggressive medical therapy, has become a R E V I E W P A P E R 8,9 These criteria have been scrutinized as researchers focus on finding possible risk stratifiers to identify patients most at risk for sudden cardiac death, which is important in increasing the costeffectiveness of the device. 8,10,11 Ventricular dysfunction is a hallmark of CHF and is frequently associated with ventricular conduction delays. Stevenson 13 In addition to coordinating atrial and ventricular contraction, biventricular cardiac pacemakers stimulate the right and left ventricles almost simultaneously as a means of resynchronizing ventricular contraction.…”
Section: Medical and Patient Management Factors Of Chf And Crt/icdsmentioning
confidence: 99%
“…Analysis of cost effectiveness in the SCD-HeFT trial showed that ICD therapy is cost effective, with incremental cost of $38,400 (95% CI of $25,217 to $80,160). This was similar in patients with ischemic and non-ischemic cardiomyopathy (Mark et al 2006). In a pooled analysis of eight primary prevention trials, ICD therapy was not found to be cost effective in CABG PATCH and in DINAMIT, which are the trials that showed no mortality benefit from ICD therapy compared to conventional medical therapy.…”
Section: Cost Effectiveness Of Icd Therapymentioning
confidence: 84%